The monotonicity of the term premium - McCulloch, J.Huston (Journal of Financial Economics, 1987)
Fama's evidence that the term premium on Treasury securities is not monotonically increasing is found to depend entirely on the behavior of bid-asked mean returns on 9- and 10-month bills, and only during the subperiod 8/64–12/72. When transactions costs, as reflected in the bid-asked spread, are taken into account, there is found to be no way to exploit this non-monotonicity. The anomalous behavior of the quotations is attributed to the Treasury's auctions of 9-month bills during the period 9/66–10/72. The hypothesis that the term premium is a monotonically increasing function of maturity remains unrefuted.